Pseudodrusen and Incidence of Late Age-Related Macular Degeneration in Fellow Eyes in the Comparison of Age-Related Macular Degeneration Treatments Trials - Zhou, Qiang; Daniel, Ebenezer; Maguire, Maureen G; Grunwald, Juan E; Martin, E Revell; Martin, Daniel F; Ying, Gui-Shuang (Ophthalmology (Rochester, Minn.), 2016)
To evaluate the association between pseudodrusen and incidence of late age-related macular degeneration (AMD) in fellow eyes of patients with unilateral neovascular AMD (nAMD). Cohort study within the Comparison of AMD Treatments Trials (CATT). Patients with neither nAMD nor geographic atrophy (GA) in the fellow eye at baseline. Presence and type (dot, reticular, or confluent) of baseline pseudodrusen were assessed using digital color fundus photography (CFP) viewed under full color, green channel, and blue channel; red-free images; and fluorescein angiography (FA). Incidence of nAMD was based on monthly clinical examination and reading center evaluation of images at years 1 and 2. Incidence of GA was based on reading center evaluation of CFP and FA images at years 1 and 2. Associations of baseline pseudodrusen with incident nAMD and GA were summarized with adjusted risk ratios (aRRs) and their 95% confidence intervals (CIs) from multivariate Cox models, with adjustment of covariates identified through backward stepwise selection. Incident nAMD and GA. Among 620 fellow eyes, 176 (28.4%) had baseline pseudodrusen (55% dot, 82% reticular, 35% confluent). Within 2 years, nAMD occurred in 54 eyes (30.7%) with pseudodrusen and in 72 eyes (16.2%) without pseudodrusen (aRR, 2.05; 95% CI, 1.43-2.93); GA occurred in 27 eyes (15.3%) with pseudodrusen and in 37 eyes (8.3%) without pseudodrusen (aRR, 1.89; 95% CI, 1.13-3.17); late AMD occurred in 73 eyes (41.5%) with pseudodrusen and in 101 eyes (22.8%) without pseudodrusen (aRR, 2.07; 95% CI, 1.51-2.83). Dot pseudodrusen were associated independently with nAMD (aRR, 2.53; 95% CI, 1.60-4.00), whereas confluent pseudodrusen were associated independently with GA (aRR, 4.35; 95% CI, 1.69-11.2). Eyes with pseudodrusen had increased incidence of late AMD regardless of whether the Age-Related Eye Diseases Study (AREDS) severity score was 2 (28.7% vs. 10.3%), 3 (34.9% vs. 13.7%), or 4 (50.5% vs. 32.0%). In fellow eyes of CATT participants, pseudodrusen were associated independently with a higher incidence of both nAMD and GA. Dot pseudodrusen were associated with nAMD, whereas confluent pseudodrusen were associated with GA. Pseudodrusen should be considered along with the AREDS severity score for predicting late AMD.